Multifactorial pathways facilitate resilience among kindergarteners at risk for dyslexia: A longitudinal behavioral and neuroimaging study. Issue 1 (21st May 2020) - Zuk, Jennifer; Dunstan, Jade; Norton, Elizabeth; Yu, Xi; Ozernov‐Palchik, Ola; Wang, Yingying; Hogan, Tiffany P.; Gabrieli, John D. E.; Gaab, Nadine
Abstract: Recent efforts have focused on screening methods to identify children at risk for dyslexia as early as preschool/kindergarten. Unfortunately, while low sensitivity leads to under‐identification of at‐risk children, low specificity can lead to over‐identification, resulting in inaccurate allocation of limited educational resources. The present study focused on children identified as at‐risk in kindergarten who do not subsequently develop poor reading skills to specify factors associated with better reading outcomes among at‐risk children. Early screening was conducted in kindergarten and a subset of children was tracked longitudinally until second grade. Potential protective factors were evaluated at cognitive‐linguistic, environmental, and neural levels. Relative to at‐risk kindergarteners with subsequent poor reading, those with typical reading outcomes were characterized by significantly higher socioeconomic status (SES), speech production accuracy, and structural organization of the posterior right‐hemispheric superior longitudinal fasciculus (SLF). A positive association between structural organization of the right SLF and subsequent decoding skills was found to be specific to at‐risk children and not observed among typical controls. Among at‐risk children, several kindergarten‐age factors were found to significantly contribute to the prediction of subsequent decoding skills: white matter organization in the posterior right SLF, age, gender, SES, and phonological awareness. These findings suggest that putative compensatory mechanisms are already present by the start of kindergarten. The right SLF, in conjunction with the cognitive‐linguistic and socioeconomic factors identified, may play an important role in facilitating reading development among at‐risk children. This study has important implications for approaches to early screening, and assessment strategies for at‐risk children. Abstract : In an effort to promote positive outcomes for kindergarteners at risk for reading difficulties, the present study examined potential protective or compensatory factors associated with better reading outcomes among at‐risk children in a longitudinal study from kindergarten to second grade. Factors on cognitive‐linguistic, environmental, and neural levels at the kindergarten age significantly differed between at‐risk children with subsequently typical versus poor reading outcomes. Moreover, kindergarten‐age factors significantly contributed to the prediction of decoding skills at the end of second grade. Findings carry implications for approaches to early screening and assessment strategies for at‐risk children.